Phase Transition of RN-AdS Black Hole with Fixed Electric Charge and Topological Charge - Shan-Quan Lan (Advances in High Energy Physics)
Phase transition of RN-AdS black hole is investigated from a new perspective. Not only is the cosmological constant treated as pressure but also the spatial curvature of black hole is treated as topological charge ϵ. We obtain the extended thermodynamic first law from which the mass is naturally viewed as enthalpy rather than internal energy. In canonical ensemble with fixed topological charge and electric charge Q, interesting van der Waals like oscillatory behavior in T-S and P-V graphs and swallow tail behavior in G-T and G-P graphs is observed. By applying the Maxwell equal area law and analysing the Gibbs free energy, we obtain analytical phase transition coexistence curves which are consistent with each other. The phase diagram is four dimensional with T,P,Q,ϵ.